KAJIAN KEARIFAN LOKAL PETANI PADI SAWAH DI DESA HUTA GURGUR II KECAMATAN SILAEN KABUPATEN TOBA SAMOSIR - Guntur, Alfensius '; Sayamar, Eri '; ', Cepriadi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Indonesia is a agraris and most of the people derive their main income in agricultural .As for initial phase in agriculture at first by doing clearing land and end result up to the harvesting , village Huta Gurgur II is one of producing rice in sub-district silaen districtToba Samosir.As for system irrigation which there is sitem irrigation simple farmers only rely on water flowing from springs mountain , in daily life farmers to the cultivation plants rice farming always used traditional ways.Local knowledge done rice farmers rice fields in village Huta Gurgur II is to make si gabe ni taon namely be grateful for activities that we do run smoothly and we stay healthy .Farming rice farming is also intended for farmers to that it strengthens kinship ties between the village community Huta Gurgur II, farmers village Huta Gurgur II use seeds superior local nursery own by farmers and the term harvest farmers starting from seeding until by planting need the time 7-9 the new moon ready to harvesting.Researchers use a method of this interviewquestionnaire, the sampling method of kuisioner snowball with the number of respondents 9 people consisting of 1 ) the village head, 2 ) religious figures, 3 ) adat leaders, 4 ) the head of the farmers 5 ) farmers rice farming .The local wisdom that existed in the village Huta Gurgur II a total of 77 the local wisdom .The local wisdom which the ancients there is now no 25 the local wisdom the local wisdom and which the ancients there are and hitherto have done a total of 52 the local wisdom the local wisdom and now there is no.   Keyword: local wisdom, paddy plants, strategy local wisdom